Communicating the brand promise to internal stakeholders in Higher Education Institutions - Kyriacou, Evdoxia; Zarkada, Anna K. (My University, 2023)
Most of the marketing of Higher Education Institutions (HEIs) literature has focused on external branding activities (Mampaey et al. 2020; Pinar, Girard, and Basfirinci 2020) but neglected inside-out brand development (Sujchaphong, Nguyen, and Melewar 2015) through Internal Marketing (IM). The IM field, however, still faces the challenge of inconsistent conceptualizations of its nature and underlying practices and has largely ignored the particularities of the HE sector, despite its social and economic importance (Qiu, Boukis, and Storey, 2021). So, the aim of this paper is to contribute to both by exploring the meaning and elements of the IM Mix (IMM) as perceived by HEI employees.
Keywords: Internal communication; Internal marketing; Internal branding; Higher education; HEIs